Commercially Important Pest Control Agents of Plant and Microbial Origin for The Management of Insect-Pests - Rana, Virendra Singh (Indian Forester, 2022)
The cultural practice was the only crop protection tool during the early days when agriculture came into existence followed by the use of natural pesticides, which included plant and mineral-based products. The earlier record showed that Sumerians used sulfur in 3000 BC while Greeks and Romans used ash, oil, and sulfur in 600BC as pest control agents. The first use of tobacco extract as a pest control product was recorded in the 1600s followed by the use of pyrethrum and other natural products for the protection of plants from pest and diseases. But after the discovery of synthetic pesticides in 1930 and onwards, many effective synthetic pesticides of organochlorine, organophosphate, carbamate, pyrethroid, and neonicotinoid groups dominated the market and the use of the cultural practices and natural products-based pest control agents declined. Now, the use of synthetic pesticides in agriculture is being discouraged due to their toxicity to non-target organisms, increasing pest resistance, undesirable environmental issues, persistence, and residues. The current regulations on synthetic pesticides are again driving the research and development on identification of alternative products, derived from plants and microbes which are effective, environmentally benign and safe to end-users. In fact, this situation is arising mainly due to misuse, over and unscientific uses of recommended pesticides, including spurious pesticides, however, without the use of synthetic pesticides, it will a challenge to feed the growing world population until effective biopesticides are made available to the end-users. Many organizations are refocusing to promote natural farming or organic agriculture in different parts of the world. Some of the natural extracts, oils, and molecules of plant origin and strobilurins, avermectins, spinosads, milbemycins from soil microbes including biocontrol agents identified as crop protection products are now available as effective substitutes to synthetic pesticides. The large-scale production of existing biopesticides and identification of newer biopesticides from microbial and plant resources need to be strengthened to support food security.